Mastic gum aided amoxicillin trihydrate gastro retentive mucoadhesive microspheres: In vivo evaluation - Sowjanya, HBM; Ahad, HA (Bangladesh Journal of Scientific and Industrial Research, 2022)
The primary objective of the study is to test gastro retentive mucoadhesive Amoxicillin trihydrate (ATH) microspheres for various in vivo properties. Several metrics were used to assess the improved ATH Mastic gum mucoadhesive microspheres (AMMM) in vitro. In vivo testing was conducted using formula-8 (AMMM-8), as suggested by prior study results by Soujanya et al., 2022. Four healthy rabbits of both sexes were used to assess the availability of plasma medicines. Pharmacokinetic parameters were measured in plasma samples. The study revealed that in vivo animal studies in rabbits showed good drug levels of ATH. After a single dose of formulation AMMM-8 (44.28mg/kg), the symmetrical mean Cmax (25.69±0.11μg/ml) tmax (6h), AUC (0-10h) (185.1±1.28 μg.h/ml), AUC (0-∞) (269.1±4.68 μg.h/ml), and AUMC (840.42±2.23 μg.h/ml) were better than ATH. According to the findings, ATH reached systemic circulation faster than the pure medication and had acceptable kinetic values. Bangladesh J. Sci. Ind. Res. 57(3), 187-194, 2022